If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(q-5=2(9+5)=
We move all terms to the left:
3(q-5-(2(9+5))=0
We add all the numbers together, and all the variables
3(q-5-(214)=0
We add all the numbers together, and all the variables
3(q-5-214=0
| 11=p/2 | | 4((x)-(5))=(4x)-(20) | | -11t+16=-14-16t-5 | | u+3/5=1/4 | | 3m+108=m^2 | | 11=p/15 | | 5=x+48/9 | | 18-5x=-6x-5x | | 9|-3x+1|-5=-5 | | P=W÷t | | 4y-3.4=5y | | 1/2(b-3)=21/2 | | -5f-2=-12-4f | | 5x+25=2x+22 | | 8=11+k | | 10=13-2(-3-3w) | | 3(X-3)=6(x+5)+2 | | -32=-3+7x3(x-2) | | 10x-30=6x-24+2.5x | | 3=-4b-10/8 | | a/5-13=12 | | 4+11(10+13x)=13x-2(x+9 | | (3x-1)+41=180 | | 5=(3/2)x-9 | | 6-2b=18+4b | | 47-2x=2x+3 | | 12w+10w+4=80 | | 12t=3 | | |5x+3|=2x-1| | | 112=-2(6x-8) | | -.5x^2+5x+1024=0 | | 5x-13=98 |